The Relationship between Students Perceptions of Interpersonal Teacher Behaviour with Students Biology Outcomes - Purba, Debora Evania; Supriyatin, S; Sigit, Diana Vivanti (Biosfer: Jurnal Pendidikan Biologi, 2015)
Interpersonal teacher behaviour is behaviors that specifically relate to how teachers interact with their students on a personal. The purpose of this study was to determine the relationship between students’ perceptions of interpersonal teacher behaviour with students’ biology outcomes. The research was conducted in January-June 2015 at the 13 Jakarta Senior High School. The method used was descriptive correlational method. The data of students’ perceptions of interpersonal teacher behaviour is colected with the Questionnaire on Teacher Interaction (QTI). Sampling was done by using Simple Random Sampling. The sample consisted of 85 students. The data tested by normality test using the Kolmogorov-Smirnov test (α = 0.05) and test homogeneity using Bartlett’s test at α = 0.05. The result showed that the data was normally distributed and homogen. The regression model is Ŷ = -85.53 + 0.96X. The correlation coefficient obtained was 0.76, which means there is a positive relationship between Students’ Perceptions of Interpersonal Teacher Behaviour with Students’ Biology Outcomes. In brief, teachers interpersonal has to be improved for getting great students learning outcome.